Analisis Bibliometrik Mengenai Metode Dakwah Wali Songo pada Database Dimensions - Ahmad Satria (UIN Sunan Gunung Djati Bandung, 2023)
Various studies related to the Wali Songo proselytizing method continue to be developed and published in various forms of scientific discourse. This research seeks to map research trends related to the Wali Songo proselytizing method by collecting and analyzing data in the last ten years. This research is a bibliometric research in the Dimensions database, namely by measuring or analyzing the development of literature with statistical techniques. There are five numbers that researchers do in conducting this study, namely the first step is determining keywords, the second step is data search, the third step is data selection, the fourth step is data validation, and the last step is data analysis. The results of this study show that the study of the Wali Songo da'wah method is quite interesting to study, this is evidenced by its productivity every year which is always increasing. Research on the Wali Songo proselytizing method can be reused by lecturers, teachers, and other stakeholders to support learning and teaching activities in the education environment.